2012
DOI: 10.1002/jor.22206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of loading history of compartments in the knee using bone SPECT/CT: A study combining alignment and 99mTc‐HDP tracer uptake/distribution patterns

Abstract: This study investigates if the mechanical/anatomical alignment influences the intensity values as well as the distribution pattern of SPECT/CT tracer uptake. Eighty-five knees (mean age 48 AE 16) undergoing 99mTc-HDP-SPECT/CT due to pain were prospectively included. SPECT/CTs were analyzed using a previously validated localization method. The maximum intensities in each femoral, tibial, and patellar joint compartment (medial, lateral, central, superior, and inferior) were noted using a color-coded grading scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 34 publications
3
95
0
3
Order By: Relevance
“…In addition, the time from surgery might have a significant impact on tracer uptake. In a previous study we have shown that a non-ideal mechanical axis such as varus or valgus aligned knee leads to increased SPECT tracer uptake in the stressed compartment [16]. However, the altered tracer uptake in patients with leg deformity is caused by mechanical stress, which is not the case in these patients after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the time from surgery might have a significant impact on tracer uptake. In a previous study we have shown that a non-ideal mechanical axis such as varus or valgus aligned knee leads to increased SPECT tracer uptake in the stressed compartment [16]. However, the altered tracer uptake in patients with leg deformity is caused by mechanical stress, which is not the case in these patients after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 93%
“…This standardised algorithm including grading and anatomical localization of SPECT/CT tracer uptake promises the identification of specific pathological tracer uptake patterns and distributions [9]. It now allows the correlation of surgical factors such as tunnel position and orientation with mechanical alignment, clinical outcome and biological factors [9,16]. It also promises the critical assessment of the osseointegration of the bonegraft-fixation complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 presents a pertinent example. In a series of carefully conducted studies, Hirschmann et al and Rasch et al [63,64] established that intensity of tracer uptake as visualized by SPECT/CT reflects the specific loading patterns of the knee with regard to its alignment and that abnormal increases in tracer uptake are reversible on tibial osteotomy correcting for varus misalignment [65,66]. Furthermore, they proposed a standardized, semiautomatic approach for the evaluation of tracer uptake in the knee in relation to component position following arthroplasty [67].…”
Section: Differential Diagnosis Of Pain Associated With the Musculoskmentioning
confidence: 99%
“…Hirschmann et al 23 reported that SPECT/CT reflects the loading pattern of the knee joint with regards to the mechanical and anatomical alignment. It is also related to the degree of osteoarthritis of the knee.…”
Section: Table 3 Standardised Maximum Intensity Of 99mtc-hdp-btu In mentioning
confidence: 99%